Effect of health education on knowledge regarding cervical carcinoma among the female college students of Nadia district, West Bengal - Debnath, Priya; Pal, Jayita; Halder, Tanudipta; Ghosh, Manoj (International Journal of Research in Medical Sciences, 2024)
Background: Cervical cancer, the second most common cancer among women globally, causes significant deaths in low- and middle-income countries, including India. This study aims to assess the effectiveness of health education on cervical cancer knowledge among female college students in Nadia district, West Bengal, highlighting the importance of awareness in this priority group. Methods: A quasi-experimental study was conducted at two government colleges in the Nadia District. It involved three steps: initially, a baseline survey was performed using a pretested questionnaire and checklist to gather socio-demographic data and assess students’ knowledge of cervical cancer. This was followed by a three-week intervention phase at the study college. Finally, knowledge scores were reassessed post-intervention at both the study and control colleges. Results: Baseline comparisons of socio-demographic characteristics and median knowledge score showed no significant difference between the study and control groups (median scores: 4.50 versus 9.00, p=0.431), indicating comparability. Post-intervention, the study college exhibited a significant increase in knowledge scores (median 19, IQR 9.00-24) compared to the control college (median 8, IQR 2.00-12.75). The control college showed no significant change in median knowledge scores post-intervention (pre-test median 9.00, IQR 3-12; post-test median 8.00, IQR 2-12.75, p=0.320). Conclusions: Structured health education programs with regular reinforcement significantly enhance college students’ knowledge of cervical cancer. An integrated approach involving both education and health departments is essential for effective implementation.